REPRESENTASI TRAUMA DAN PROSES PEMULIHAN DIRI DALAM NOVEL ROOM KARYA EMMA DONOGHUE - Shelly Aulia Pratiwi (FRASA: Jurnal Keilmuan, Bahasa, Sastra, dan Pengajarannya, 2026)
This study aims to analyze the representation of trauma and the process of trauma recovery experienced by the characters Ma and Jack in Emma Donoghue’s novel Room. Trauma has been widely explored in literary studies, but research that specifically examines both the representation of trauma and the recovery process in Room remains limited. This study employs a qualitative descriptive method with a textual analysis approach. The data consist of narrative excerpts, dialogues, and descriptions of events in the novel, collected through close reading and analyzed using thematic analysis. The results show that trauma in Room is represented through fragmented language, repetition, and silence. Fragmented language appears in Jack’s limited understanding of the world and in Ma’s use of symbolic language to explain the reality outside Room. Repetition is reflected in routines that function as a survival mechanism, while silence appears in restrained language and in traumatic experiences that are difficult to express fully. The process of trauma recovery takes place through the stages of safety, remembrance and mourning, and reconnection. Thus, Room not only portrays the impact of trauma, but also shows that recovery unfolds gradually through the rebuilding of safety, the processing of painful memories, and the rebuilding of life. KEYWORDS: Cathy Caruth; Judith Herman; Room; Trauma.